PEMBERDAYAAN EKONOMI PEREMPUAN MELALUI PELATIHAN KEUANGAN PADA INDUSTRI RUMAHAN - Pratiwi, Laras; Somantri, Yeni Fitriani; Rahayu, Intan (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
The PPPA Ministry since 2016 has been implementing Women's Economic Empowerment activities through the development of Home Industry Actors (IRs). Home Industry (IR), which is a micro-scale industry, generally utilizes or produces products in the form of finished goods that provide added value and are done at home, specifically or even as part-time work (Kemenppa, 2018). One type of home industry that can be run by a housewife is production or trade on a small scale whose operational processes can be carried out at home both directly and virtually. Problems arise when financial management and bookkeeping processes are not going well. The purpose of this community service activity is to provide education to Home Industry players regarding financial management. This activity provides benefits for home industry players. The process of recording financials in an orderly manner can provide an overview of the company's financial condition and can consider in decision making. Community service activities are carried out through three stages. First is the preparation stage; the second is the implementation phase of the event, and the third is the evaluation phase. The results of this community service activity are the understanding of the financial records of home industry owners in the Al-Mahabbah Foundation environment, the home industry players have been able to record company finances based on the applicable financial statements.